Correction: Impact of corporate social responsibility on employee loyalty: Mediating role of person-organization fit and employee trust. - Hebo Jin; Xuexiao Li; Guangsen Li (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300933.].